Iron Status and Physical Performance in Athletes - Andrea Solberg; Håkon Reikvam (Life, 2023)
Iron is an important mineral in the body, essential for muscle function and oxygen transport. Adequate levels of iron in the blood are necessary for athletes, as iron-deficiency anemia can reduce physical performance. Several studies have investigated iron status and supplementation in iron-deficient athletes, and determined how physical strain can change iron balance and markers related to iron status. The question of how to influence and optimize iron status, as well as other markers that can affect iron metabolism, has been less thoroughly investigated. Therefore, the aim of this review is to take a closer look at the importance of iron values, iron markers, and factors that can change iron metabolism for physical performance and the extent to which physical performance can be influenced in a positive or negative way. A systematic search of the PubMed database was performed, with the use of « iron» or «iron deficiency» or «hemoglobin» AND «athletes» AND «athletic performance» as a strategy of the search. After the search, 11 articles were included in the review after the application of inclusion and exclusion criteria. Major findings include that iron supplementation had the best effect in athletes with the lowest iron status, and effects on physical performance were mostly achieved in those who were originally in a deficit. Iron supplementation could be beneficial for optimal erythropoietic response during altitude training, even in athletes with normal iron stores at baseline, but should be performed with caution. Alteration of the hepcidin response can affect the use of existing iron stores for erythropoiesis. Energy intake, and the amount of carbohydrates available, may have an impact on the post-exercise hepcidin response. Optimal vitamin D and B12 levels can possibly contribute to improved iron status and, hence, the avoidance of anemia.